Schistosoma mansoni infection as a trigger to collapsing glomerulopathy in a patient with high-risk APOL1 genotype. - Precil D Neves; Ramaiane A Bridi; Janaína A Ramalho; Lectícia B Jorge; Elieser H Watanabe; Andreia Watanabe; Luis Yu; Viktoria Woronik; Rafaela B Pinheiro; Leonardo A Testagrossa; Lívia B Cavalcante; Denise M Malheiros; et al. (Public Library of Science (PLoS), 2020)
Background Schistosoma mansoni schistosomiasis (SM) remains a public health problem in Brazil. Renal involvement is classically manifested as a glomerulopathy, most often membranoproliferative glomerulonephritis or focal and segmental glomerulosclerosis. We report a case of collapsing glomerulopathy (CG) associated with SM and high-risk APOL1 genotype (HRG). Case report A 35-year-old male was admitted for hypertension and an eight-month history of lower-limb edema, foamy urine, and increased abdominal girth. He had a recent diagnosis of hepatosplenic SM, treated with praziquantel, without clinical improvement. Laboratory tests revealed serum creatinine 1.89mg/dL, blood urea nitrogen (BUN) 24mg/dL, albumin 1.9g/dL, cholesterol 531mg/dL, low-density lipoprotein 426mg/dL, platelets 115000/mm3, normal C3/C4, antinuclear antibody (ANA), rheumatoid factor (RF), and antineutrophil cytoplasmic antibodies (ANCA), negative serologies for hepatitis C virus (HCV) and human immunodeficiency virus (HIV), HBsAg negative and AntiHBc IgG positive, no hematuria or leukocyturia, 24 hour proteinuria 6.56g and negative serum and urinary immunofixation. Kidney biopsy established the diagnosis of CG. A treatment with prednisone was started without therapeutic response, progressing to end-stage kidney disease 19 months later. Molecular genetics investigation revealed an HRG. Conclusions This is the first report of CG associated with SM in the setting of an HRG. This case highlights the two-hit model as a mechanism for CG pathogenesis, where the high-risk APOL1 genotype exerts a susceptibility role and SM infection serves as a trigger to CG.